2018
DOI: 10.3390/su10010174
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Integration of Climate Change and Development Strategies at Local Levels: Insights from Muheza District, Tanzania

Abstract: Integration of climate change measures in local development planning and delivery of Climate Compatible Development (CCD) at local levels is widely advocated to assist achievement of the Sustainable Development Goals. Such integration is not straightforward, and limited knowledge on multi-level governance of CCD exists. To progress this critical enquiry, we build on the concept of Climate Policy Integration (CPI) to assess how climate change measures are integrated in local development planning. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Building individual capacities certainly leads to household resilience, but these also need to be coordinated by households themselves and get support from right policies. As indicated by Pilato, Sallu, and Gaworek‐Michalezenia (), climate governance is relevant for integrated planning and policymaking across a variety of sectors. It recognises that national policy frameworks facilitate a strong top‐down approach that requires coordinated governance institutions that are able to translate higher level policy into local action plans (Corfee‐Morlot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Building individual capacities certainly leads to household resilience, but these also need to be coordinated by households themselves and get support from right policies. As indicated by Pilato, Sallu, and Gaworek‐Michalezenia (), climate governance is relevant for integrated planning and policymaking across a variety of sectors. It recognises that national policy frameworks facilitate a strong top‐down approach that requires coordinated governance institutions that are able to translate higher level policy into local action plans (Corfee‐Morlot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the adaptation practices have been discovered in Indonesia's municipalities, such as building adaptive capacity (e.g., research, awareness-raising, training, and advocacy), creating a suitable institutional environment (e.g., city team workforce), and implementing adaptation (e.g., mangrove plantation) [43]. From the previous studies [9,38,[44][45][46], some influencing drivers for integration process can be found, including the officers' motivation, initiative, and leadership, the assistance, and support by government and international development agencies, the existence of policy direction and guideline as well as the political will of decision-makers.…”
Section: Drivers and Benefits Of The Integration Strategymentioning
confidence: 99%
“…The authors in [5] demonstrate that the urbanization process affects climate at all scales. Several studies have shown strategies to minimize the impact of growth and of urban density on climate using urban planning as a tool to control land usage and coverage, as well as reduce the impact of the urbanization process [6][7][8]16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The relation between the urbanization process and climate is complex.…”
Section: Urban Morphology and Climatementioning
confidence: 99%
“…Different methods and techniques exist to analyze urban morphological indices, ranging from the use of spatial metrics [31][32][33][34][42][43][44], as is the case of the present study, to the use of satellite images [45][46][47][48][49][50]. Several indices may be used in such analyses, such as aerodynamic roughness, porosity, building density, verticality, H/W ratio, and impervious surface fraction, helping to minimize the impacts caused by city growth.…”
Section: Urban Morphology Indicesmentioning
confidence: 99%